2021
DOI: 10.1111/dpr.12520
|View full text |Cite
|
Sign up to set email alerts
|

How culture may nurture institutional trust: Insights from Bangladesh and Nepal

Abstract: Motivation Most studies of the normative roots of political trust argue that they stem from policy performance rather than from cultural orientation. That sits at odds with the observation that institutional trust—that is, citizens’ confidence in public agencies—is high in Bangladesh and Nepal despite poor policy performance. Purpose The article assesses the influence of policy performance and cultural orientation of citizens in Bangladesh and Nepal on institutional trust. Approach and Methods The article draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Bosnians, Montenegrins and Slovenians who valued tradition, conformity and safety reported higher, but Bulgarians, Croatians and Kosovars who valued tradition reported lower institutional trust. Again, this might suggest that adolescents and emerging adults from the former group of countries might perceive the institutions under study as drivers of stability, corroborating previous findings on the role of authoritarianism as cultural characteristic related to higher levels of institutional trust ( Jamil and Baniamin, 2020 ). Conversely, in the latter group of countries, these institutions might be perceived as a threat to the established tradition and social order, for example by promoting ideas conflicting with those values.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Bosnians, Montenegrins and Slovenians who valued tradition, conformity and safety reported higher, but Bulgarians, Croatians and Kosovars who valued tradition reported lower institutional trust. Again, this might suggest that adolescents and emerging adults from the former group of countries might perceive the institutions under study as drivers of stability, corroborating previous findings on the role of authoritarianism as cultural characteristic related to higher levels of institutional trust ( Jamil and Baniamin, 2020 ). Conversely, in the latter group of countries, these institutions might be perceived as a threat to the established tradition and social order, for example by promoting ideas conflicting with those values.…”
Section: Discussionsupporting
confidence: 86%
“…They found that values such as security, conformity, tradition and power were positively associated with institutional trust, while the associations with self-direction, universalism and hedonism were negative. A similar pattern of relationships between cultural values and institutional trust was found by Jamil and Baniamin (2020) —high authoritarian cultural orientation is positively associated with trust in public institutions. Marketing research also confirms the role of individual values ( Shiu et al, 2015 ) and cultural values ( Wu and Shen, 2018 ) in institutional trust in key actors of the economic system.…”
Section: Introductionsupporting
confidence: 66%
“…The existing literature on trust often focuses on two potential sources of trust: The cultural background of migrants and the institutional context (see Dinesen, 2013 for an overview). The cultural perspective assumes trust to be rather stable over time and to be passed on from one generation to the next (e.g., Buchan et al, 2002;Uslaner, 2002Uslaner, , 2008Sønderskov and Dinesen, 2016;Jamil and Baniamin, 2021;Karaja and Rubin, 2021). The institutional perspective, on the other hand, assumes that trust can change over time and focuses on experiences with high-or low-quality institutions in a country (e.g., Levi, 1996;Rothstein and Stolle, 2008;Freitag and Bühlmann, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In cases like Nepal, high trust in low-performing governments may be attributed to a culture of obedience and loyalty to the government. Therefore, perceptions of information disclosure, visibility, and citizen participation may be more critical to citizensʼ trust in the Nepalese government than the actual performance itself (Jamil & Baniamin, 2021).…”
Section: Nepalese Contextmentioning
confidence: 99%